THE RELATIONSHIP BETWEEN TRUST AND ORGANIZATIONAL RESILIENCE AMONG EMPLOYEES AT WORKPLACE - Chaudhary, Ananta; Ashutosh, Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Trust in an organization is very important. Companies with high levels of trust experience more engagement and resilience in case of challenges. The study’s aim is to determine the level of trust on organizational resilience in workplace. The object is to investigate the degree of organizational resilience and trust that employees have in their workplace. It was hypothesized that trust and organizational resilience in the workplace will be significantly correlated. Tools used are Trust Scale and the Resilience scale. Results show that higher levels of trust increases resilience among the employees and they tend to work more efficiently in the organization. Therefor trust acts as a pivotal part of any organization and leads to effective communication, collaboration , and leading them to face any challenges.